2003
DOI: 10.1159/000073642
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Protects against Necrotizing Enterocolitis of Newborn Rats by the Inhibiting Nitric Oxide Formation

Abstract: Background: Necrotizing enterocolitis (NEC) is an important neonatal disease with a high mortality rate; erythropoietin (Epo) is a hematopoietic growth factor. Functional Epo receptors are in the fetal and postnatal small bowel and their ligands are available for binding. Excessive nitric oxide (NO) production by an isoform of NO synthase inducible by inflammatory stimuli leads to changes in vascular permeability and tissue injury. The aim of this study was to investigate NO formation in an experimental model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
1
26
0
2
Order By: Relevance
“…However, these studies have not identified the responsible mediators, examined NO levels in endothelial cells or identified a molecular mechanism to explain the recruitment of Cav1 to caveolae. Based on our findings it might be interesting to examine the role of sphingomyelinase in these and other clinically relevant situations [44,45] that are characterised by reduced NO production.…”
Section: Role Of No In Paf-induced Oedema Formationmentioning
confidence: 88%
“…However, these studies have not identified the responsible mediators, examined NO levels in endothelial cells or identified a molecular mechanism to explain the recruitment of Cav1 to caveolae. Based on our findings it might be interesting to examine the role of sphingomyelinase in these and other clinically relevant situations [44,45] that are characterised by reduced NO production.…”
Section: Role Of No In Paf-induced Oedema Formationmentioning
confidence: 88%
“…In premature rabbits exposed to hyperoxia, rhEPO decreased the plasma iron concentration and increased the ability of plasma to inhibit lipid peroxidation (7). In addition, EPO may increase the activity of protective enzymes of oxidative injury and modulate the production of nitric oxide, a major mediator of tissue injury (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Recent Cochrane analyses of early [77] and late [52] rEPO usage concluded that there was a reduction in the number and volume of RBCT but the clinical significance was questioned. Other hypotheses include: (1) protection against ischaemia/reperfusion injury in adult rats [78], (2) preservation of the intestinal barrier function in a rat NEC model [79], (3) inhibition of nitric oxide production [80], and (4) reduction of inflammatory mediators and apoptosis [81]. A recent human study in China [82] showed that in 94 infants with NEC, those treated with rEPO ( n = 52) compared to controls ( n = 42) had significantly lower levels of TNF-α and IL-6 and a significantly lower death and complication rate ( p < 0.05).…”
Section: Anaemia Blood Transfusion and Necmentioning
confidence: 99%